The Montessori didactic materials in the teaching of elementary mathematics concepts - Bernaldez, Pedro Bordeos 1949 (1972)
This paper is aimed at the description of selected Montessori didactic materials and the design of activities which make use of said materials in the teaching of selected mathematical concepts. The materials described include the bead bars, the bead chains and the geometric insets. The activity-oriented method of teaching was also discussed as a tool in learning as discovery. The writer believes that this method is indespensable part of the discovery approach but should not be used as an excuse for the teacher to remain idle. Recommendations on the inclusion of geometry as a wider subject area was taken as the author advocates the idea. This whole paper is an attempt to contribute to the continuous growth of elementary mathematics curriculum.
Thesis (M.A. Mathematics Education)--University of the Philippines College of Education, Diliman.
Keywords: Mathematics -- Study and teaching (Elementary) -- Philippines; Montessori method of education -- Philippines; Mathematics teachers -- Training of -- Philippines